2014
DOI: 10.1152/ajpheart.00441.2014
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NLRP3 inflammasome in CVB3-induced viral myocarditis

Abstract: Viral myocarditis, which is most prevalently caused by coxsackievirus B3 (CVB3) infection, is a serious clinical condition characterized by cardiac inflammation. Inflammasome plays an essential role in the regulation of diverse inflammatory responses by serving as a platform for caspase-1 activation and caspase-1-dependent proteolytic maturation and secretion of IL-1␤. Although inflammasome has been reported to be crucial for the development of many inflammatory diseases, its role in the pathogenesis of viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 50 publications
(54 reference statements)
3
88
1
Order By: Relevance
“…NLRP3 inflammasome activation in CMs has been described during viral myocarditis after coxsackievirus B3 infection (35). Inhibition of inflammasome activation with a pan‐caspase‐1 inhibitor resulted in reduced intensity of myocardial injury in this model along with improved cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 inflammasome activation in CMs has been described during viral myocarditis after coxsackievirus B3 infection (35). Inhibition of inflammasome activation with a pan‐caspase‐1 inhibitor resulted in reduced intensity of myocardial injury in this model along with improved cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 is the primary activator of the inflammatory cytokines IL-1B and IL-18, and plays a major role in the pathogenesis of viral myocarditis 16,31,32 . A previous study showed that heart tissue from patients with viral myocarditis had increased caspase-1 expression, and the intensity of expression was directly related to the severity of heart failure and lack of functional recovery at 6 months 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-1β is known to be also involved in a variety of cellular activities, including cell proliferation, differentiation, and apoptosis [22]. In addition to its pathophysiologic role in host protection, IL-1β pro- motes the progression of a number of autoimmune diseases: autoimmune thyroid diseases [23], diabetes mellitus [24], multiple sclerosis [25], and myocarditis [26]. IL-1β is also associated with febrile seizures [27], epilepsy [28], and gout [29].…”
Section: Discussionmentioning
confidence: 99%